Circulating versus lipopolysaccharide-induced inflammatory markers as correlates of subthreshold depressive symptoms in older adults. (13th September 2020) - Lee, S. Melanie; Te, Silena; Breen, Elizabeth C.; Olmstead, Richard; Irwin, Michael R.; Cho, Joshua H.
Abstract: Objectives: Circulating cytokines have been associated with depression, but their detection has limitations, which may be overcome by direct detection of intracellular cytokines (ICCs) after lipopolysaccharide (LPS) stimulation in vitro . This study compared circulating versus LPS-induced inflammatory markers as correlates of subthreshold depressive symptoms. Methods: Secondary data analysis of a cross-sectional insomnia study in healthy community-dwelling older adults was conducted. In 117 participants (≥55 years), plasma tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP) and in vitro LPS-induced monocyte production of IL-6 and TNF-α were assayed. Depressive symptoms were assessed using the clinician-rated Inventory of Depressive Symptomatology (IDS-C). Multivariate linear regression was conducted to test the associations between inflammatory markers and subthreshold depressive symptoms in the entire sample as well as in subgroups stratified into higher and lower inflammation levels. Results: LPS-induced TNF-α (adjusted β = 0.28, p = .04), IL-6 (0.29, p = .03) and TNF-α + IL-6 (0.43, p = .001) significantly positively correlated with subthreshold depressive symptoms only in higher inflammation subgroups. No circulating biomarkers positively correlated in any subgroups. In the entire sample, no biomarkers were significantly associated with subthreshold depressive symptoms. Conclusions: LPS-induced cytokines may be more sensitive correlates of subthreshold depressive symptoms than circulating cytokines, particularly in older adults with higher systemic inflammation. Clinical Trials Registry: ClinicalTrials.gov NCT00280020.